Analisis Pengaruh Persepsi Kualitas, Motivasi, Dan Sikap Konsumen Terhadap Keputusan Pembelian Sepeda Motor Honda Scoopy Studi Kasus Pada Pembelian Sepeda Motor Honda Scoopy) - Novi Ana Lestari; Siti Asiyah; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstraction This study aims to (1) test and analyze the perceived quality, motivation, and attitudes of consumers simultaneously on purchasing decisions, (2) test and analyze the quality of purchasing decisions, (3) test and analyze motivation on purchasing decisions (4) test and analyze the quality of purchasing decisions. analyze consumer attitudes towards purchasing decisions. This type of research is descriptive with a quantitative approach. The variables in this study consisted of perceived quality, motivation, consumer attitudes, and purchasing decisions. The population criteria in this study were active students of the 2018 Faculty of Economics and Business, the sampling technique used was purposive sampling and data collection through questionnaires directly (offline) to 60 respondents according to the population criteria. The data analysis used in this research is validity test, reliability test, normality test, classical assumption test, classical assumption test, coefficient of multiple regression analysis (R2), and hypothesis testing. on purchasing decisions simultaneously, partially perceived quality, motivation and consumer attitudes have a positive and significant effect on purchasing decisions for Honda Scoopy motorcycles. Keywords : Perception of Quality, Motivation, and Consumer Attitude towards Purchase Decision.